Human Y chromosome azoospermia factors (AZF) mapped to different subregions in Yq11 - Vogt, Peter H.; Edelmann, A.; Kirsch, S.; Henegariu, Octavian; Hirschmann, P.; Kiesewetter, F.; Köhn, F. M.; Schill, W. B.; Farah, S.; Ramos, C.; Hartmann, Martin; Hartschuh, Wolfgang; et al. (Human molecular genetics, 1996)
In a large collaborative screening project, 370 men with idiopathic azoospermia or severe oligozoospermia were analysed for deletions of 76 DNA loci in Yq11. In 12 individuals, we observed de novo microdeletions involving several DNA loci, while an additional patient had an inherited deletion. They were mapped to three different subregions in Yq11. One subregion coincides to the AZF region defined recently in distal Yq11. The second and third subregion were mapped proximal to it, in proximal and middle Yq11, respectively. The different deletions observed were not overlapping but the extension of the deleted Y DNA in each subregion was similar in each patient analysed. In testis tissue sections, disruption of spermatogenesis was shown to be at the same phase when the microdeletion occurred in the same Yq11 subregion but at a different phase when the microdeletion occurred in a different Yq11 subregion. Therefore, we propose the presence of not one but three spermatogenesis loci in Yq11 and that each locus is active during a different phase of male germ cell development. As the most severe phenotype after deletion of each locus is azoospermia, we designated them as: AZFa, AZFb and AZFc. Their probable phase of function in human spermatogenesis and candidate genes involved will be discussed.